2021
DOI: 10.1177/19476035211047628
|View full text |Cite
|
Sign up to set email alerts
|

The Releasate of Avascular Cartilage Demonstrates Inherent Pro-Angiogenic Properties In Vitro and In Vivo

Abstract: Objective Cartilage is avascular and numerous studies have identified the presence of single anti- and pro-angiogenic factors in cartilage. To better understand the maintenance hyaline cartilage, we assessed the angiogenic potential of complete cartilage releasate with functional assays in vitro and in vivo. Design We evaluated the gene expression profile of angiogenesis-related factors in healthy adult human articular cartilage with a transcriptome-wide analysis generated by next-generation RNAseq. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In cancellous and inter-cortical bone regions, the recruited MSCs aggregate, proliferate and differentiate into chondrocytes. They secrete an avascular cartilage matrix, and the granulation tissue is gradually replaced by the fibrocartilage- and hyaline cartilage-rich soft callus ( Nossin et al, 2021 ). Along with new blood vessel formation, endothelial cells, osteoblasts, and chondrocytes secrete matrix metalloproteinases to degrade the cartilage matrix.…”
Section: Overview Of Bone Healing Processmentioning
confidence: 99%
“…In cancellous and inter-cortical bone regions, the recruited MSCs aggregate, proliferate and differentiate into chondrocytes. They secrete an avascular cartilage matrix, and the granulation tissue is gradually replaced by the fibrocartilage- and hyaline cartilage-rich soft callus ( Nossin et al, 2021 ). Along with new blood vessel formation, endothelial cells, osteoblasts, and chondrocytes secrete matrix metalloproteinases to degrade the cartilage matrix.…”
Section: Overview Of Bone Healing Processmentioning
confidence: 99%
“…4). The proangiogenetic effect without immune cells has been observed for avascular cartilage ( 83 ). Studies suggest that the nerve fibers can signal pain when inflammatory cytokines are present ( 6 , 30 ).…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we investigated the changes in angiogenic potential that occur during the mineralisation of hMSC-derived cartilage. While the pro-angiogenic potential of tissue-engineered cartilage is well documented [ 4 , 31 , 32 ], the manner in which mineralisation specifically affects angiogenesis still requires investigation. Here, we optimised an in vitro strategy to induce the mineralisation of hMSC-derived chondrogenic pellets and characterised the cellular and matrix changes that occur overtime.…”
Section: Discussionmentioning
confidence: 99%
“…The withdrawal of TGF-β itself led to a drop in the production of VEGFA by the pellets and a reduction in their ability to stimulate HUVEC migration. TGF-β has a variety of biophysical effects on MSCs [ 56 , 57 ], and it was reported that angiogenic factors, such as hepatocyte growth factor (HGF), angiogenin (ANG) or VEGFA, can be released from MSCs exposed to TGF-β [ 31 , 32 , 45 , 57 ]. BGP-driven mineralisation further exacerbated this loss of pro-angiogenic potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation